Rancang Bangun Aplikasi Steganografi Berbasis Web Menggunakan Metode Least Significant Bit (LSB) Dan XOR Untuk Enkripsi File Berbasis Citra - Indra Firmansyah; Bayu Winata; Diana Azkia; Rahmatul Ula (JIKUM: Jurnal Ilmu Komputer, 2026)
Data security is vital in digital exchange, yet standard Least Significant Bit (LSB) steganography remains vulnerable to unauthorized extraction. This study aims to develop a web-based steganography application combining LSB with Exclusive OR (XOR) encryption to enhance confidentiality. The proposed method involves encrypting secret data using XOR operations before embedding it into the cover image's LSB. The application is built on a web platform for accessibility, and the resulting image quality is evaluated using Mean Square Error (MSE) and Peak Signal-to-Noise Ratio (PSNR). The results demonstrate that the system successfully embeds and extracts data intactly. The obtained PSNR values exceed 40 dB, indicating that the stego-images maintain high visual fidelity indistinguishable from the original images, thereby offering a robust solution for secure data transmission.